Brutal wars and a malevolent peace: anatomy of US policy in Iraq - Muralidharan, Sukumar
The cost of a botched peace in Iraq would be even higher than the price of a bloody war. The world community has to decide how best it can hold the US accountable for its crimes in Iraq. The alternative - acquiescence in the hit and run strategy that the US has raised to a find art in the last few decades - would be an unaffordable luxury in the current state of international relations. - Reproduced.
Keywords: War; Peace; United States - Foreign relations - Iraq; International relations